Clinical-epidemiological and pharmacoepidemiological investigation of acute cerebrovascular accidents - Oksana R. Levytska, Bohdan P. Hromovyk, Liana M. Unhurian, Kateryna V. Kostyana (Journal of Applied Pharmaceutical Science, 2017)
Acute cerebrovascular accidents belong to leading causes of disability and death worldwide, in Ukraine in particular. Hence, proper medical-and-pharmaceutical aid is crucial for the positive outcomes. Our clinical-epidemiological analysis of inpatient medical records showed that ACVA occurred in 77.6% of male and 76.0% of female patients aged 50 and over. Cerebral infarction was diagnosed in 50.3% of patients, 44.3% – sequelae of cerebrovascular disease, and 8.7% – cerebral hemorrhage. Hypertension was the prevalent concomitant disorder, with the rate of 82.0% of cases. The content-, frequency-, ABC, ATC/DDD, DU 90% analyses, and generalization allowed establish the trends, amounts and structure of drug consumption. Among 198 of drugs, the max specific weight belonged to those effecting on cardiovascular system (29.8%). We identified 8 most frequently prescribed drugs. High rates of consumption were typical for 3 drugs. The 90% of consumed DDDs accounted for 45 drugs. Atorvastatin, Dexamethasone, and Enoxaparin were characterized by high numbers of DDDs per 100 bed-days. Consumption of antihypertensive, anticoagulant and antiplatelet agents intended for basic and specific therapy, and secondary prevention of ACVA, equaled 58.0% of the total DDDs’ number. Results of the research may act as a background for rational drug prescribing for patients with ACVA.
Keywords: Acute cerebrovascular accidents, drug prescribing, treatment, drug consumption.